Crystallization and preliminary X-ray crystallographic studies of a Lys49-phospholipase A(2) homologue from Bothrops pirajai venom complexed with rosmarinic acid - dos Santos, Juliana I. [UNESP]; Santos-Filho, Norival A.; Soares, Andreimar M.; Fontes, Marcos R. M. [UNESP] (Wiley-Blackwell, 2010)
PrTX-I, a noncatalytic and myotoxic Lys49-phospholipase A(2) from Bothrops pirajai venom, was crystallized in the presence of the inhibitor rosmarinic acid (RA). This is the active compound in the methanolic extract of Cordia verbenacea, a plant that is largely used in Brazilian folk medicine. The crystals diffracted X-rays to 1.8 angstrom resolution and the structure was solved by molecular-replacement techniques, showing electron density that corresponds to RA molecules at the entrance to the hydrophobic channel. The crystals belong to space group P2(1)2(1)2(1), indicating conformational changes in the structure after ligand binding: the crystals of all apo Lys49-phospholipase A(2) structures belong to space group P3(1)2(1), while the crystals of complexed structures belong to space groups P2(1) or P2(1)2(1)2(1).